2004
DOI: 10.1037/0021-843x.113.4.569
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Ability and Risk for Alcoholism: Short-Term Memory Capacity and Intelligence Moderate Personality Risk for Alcohol Problems.

Abstract: This study tested the hypothesis that short-term memory (STM) capacity moderates the effect of social deviance on alcohol problems. Personality, cognitive ability, and alcohol use and abuse were assessed in the adult offspring of alcoholics (FHPs; n = 153) and the adult offspring of nonalcoholics (FHNs; n = 150). The results revealed that STM capacity moderated the effect of social deviance on alcohol problems, independent of intelligence. High social deviance and high-STM participants had fewer alcohol proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
126
5
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(145 citation statements)
references
References 73 publications
13
126
5
1
Order By: Relevance
“…Grenard et al (2008) in their study reported that associations related to drug among adolescents exposed to low working memory capacity compared to individuals with high working memory capacity are stronger forecasts for alcohol and cigarette abuse. Ellingson et al (2004) obtained the same results with the findings of research by Finn & Hall (2004). According to recent study, it has been displayed that interaction between working memory capacity and social deviation forecasts alcohol involvement for three years.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Grenard et al (2008) in their study reported that associations related to drug among adolescents exposed to low working memory capacity compared to individuals with high working memory capacity are stronger forecasts for alcohol and cigarette abuse. Ellingson et al (2004) obtained the same results with the findings of research by Finn & Hall (2004). According to recent study, it has been displayed that interaction between working memory capacity and social deviation forecasts alcohol involvement for three years.…”
Section: Discussionsupporting
confidence: 80%
“…No effect of working memory capacity on risky decision making displays moderator role of working memory capacity on impulsivity (Amos, Tash, Sussman, & Stock, 2008;Tash, Amos, Sussman, & Stock, 2008;Ellingson et al, 2014). Finn & Hall (2004) reported in their research that social deviation (impulsivity) has stronger bond with the problems related to alcohol among the participants with low working memory capacity compared to the individuals with higher working memory capacity. Further, individuals with high social deviation and low short-term memory capacity than the individuals with high social deviation and high short-term memory capacity have reported higher scores in Michigan Alcoholism Screening Test (MAST).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 presents the number of positive diagnoses by group and gender. Personality traits reflecting antisocial tendencies (Finn & Hall, 2004) were assessed using the Psychopathic Deviance scale of the MMPI-2 (MMPI_Pd) (Hathaway & McKinley, 1989), the Socialization scale of the California Psychological Inventory (CPI_So) (Gough, 1969), and the sum of Conduct Disorder and Antisocial Personality Disorder symptom counts from the CDIS (CD_ASPD). Research shows that these different measures of personality and antisocial symptoms are significantly associated with disadvantageous decisions on the IGT in young adult samples (Mazas et al, 2000;Stout et al, 2005).…”
Section: Psychodiagnostic and Personality Assessmentmentioning
confidence: 99%